Iron oxide coated gold nanorods synthesis, characterization, and magnetic manipulation - Gole, Anand (Langmuir : the ACS journal of surfaces and colloids, 2008)
We report a simple process to generate iron oxide coated gold nanorods. Gold nanorods, synthesized by our three-step seed mediated protocol, were coated with a layer of polymer, poly(sodium 4-styrenesulfonate). The negatively charged polymer on the nanorod surface electrostatically attracted a mixture of aqueous iron(II) and iron(III) ions. Base-mediated coprecipitation of iron salts was used to form uniform coatings of iron oxide nanoparticles onto the surface of gold nanorods. The magnetic properties were studied using a superconducting quantum interference device (SQUID) magnetometer, which indicated superparamagnetic behavior of the composites. These iron oxide coated gold nanorods were studied for macroscopic magnetic manipulation and were found to be weakly magnetic. For comparison, premade iron oxide nanoparticles, attached to gold nanorods by electrostatic interactions, were also studied. Although control over uniform coating of the nanorods was difficult to achieve, magnetic manipulation was improved in the latter case. The products of both synthetic methods were monitored by UV-vis spectroscopy, zeta potential measurements, and transmission electron microscopy. X-ray photoelectron spectroscopy was used to determine the oxidation state of iron in the gold nanorod-iron oxide composites, which is consistent with Fe2O3 rather than Fe3O4. The simple method of iron oxide coating is general and applicable to different nanoparticles, and it enables magnetic field-assisted ordering of assemblies of nanoparticles for different applications